2015
DOI: 10.1159/000430240
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Autophagy by Chloroquine Stimulates Nitric Oxide Production and Protects Endothelial Function during Serum Deprivation

Abstract: Background/Aims: Autophagy plays a fundamental role in cell survival under stress conditions such as nutrient deprivation. Decreased nitric oxide (NO) production, which may contribute to vascular dysfunction, is one of the consequences of autophagy in endothelial cells. The antimalarial drug chloroquine (CLQ) inhibits autophagy by blocking autophagosome formation and has been proposed as adjuvant chemotherapy in other diseases. Methods: Autophagy was induced by serum deprivation in Human Umbilical Vascular End… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 38 publications
(38 reference statements)
2
19
0
Order By: Relevance
“…Interestingly, the improvements in endothelial function we observed after chloroquine treatment in SHR could be attributed to improvements in both eNOS activity (even though there were no differences in basal phospho-eNOS Ser1177 expression) and decreases in ROS. Overall, our results are very much in agreement with others whom have reported that chloroquine and hydroxychloroquine are able to improve endothelium relaxation via increased NO bioavailability and decreased ROS in arteries from healthy [51] and diseased [15] rodents. Nonetheless, the underlying mechanisms for these improvements in endothelial function have been attributed to other sources of ROS, including NADPH-oxidase [15], and stimulation of NOS by chloroquine directly [51].…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, the improvements in endothelial function we observed after chloroquine treatment in SHR could be attributed to improvements in both eNOS activity (even though there were no differences in basal phospho-eNOS Ser1177 expression) and decreases in ROS. Overall, our results are very much in agreement with others whom have reported that chloroquine and hydroxychloroquine are able to improve endothelium relaxation via increased NO bioavailability and decreased ROS in arteries from healthy [51] and diseased [15] rodents. Nonetheless, the underlying mechanisms for these improvements in endothelial function have been attributed to other sources of ROS, including NADPH-oxidase [15], and stimulation of NOS by chloroquine directly [51].…”
Section: Discussionsupporting
confidence: 93%
“…On the contrary, several lines of evidence indicated that autophagy plays a harmful role in atherosclerosis. Inhibition of autophagy stimulates nitric oxide production and protects endothelial function [47]. Autophagic death of SMCs results in plaque destabilization owing to the reduced synthesis of collagen and thinning of the fibrous cap [48].…”
Section: Discussionmentioning
confidence: 99%
“…35 Although several recent studies have reported the promising effect of CQ on the endothelialdependent vascular relaxation via increasing the release of nitric oxide in endothelial cells, 21,36 the efficiency of CQ application over the ischemic diseases is still largely controversial. [13][14][15] The effect of CQ on the cell cycle arrest caused by nutrient deciency in endothelial cells and the underlying mechanisms have not been fully characterized.…”
Section: Discussionmentioning
confidence: 99%